Prioritizing sufficient dose to gross tumor volume over normal tissue sparing in intensity‐modulated radiotherapy treatment of T4 nasopharyngeal carcinoma. Issue 5 (1st March 2023) - Chen, Yanyan; Zhang, Quxia; Lu, Tianzhu; Hu, Cairong; Zong, Jingfeng; Xu, Yun; Zheng, Wei; Chen, Lisha; Lin, Senan; Qiu, Sufang; Xu, Luying; Pan, Jianji; et al.
Abstract: Background: In intensity‐modulated radiation therapy (IMRT) for nasopharyngeal carcinoma (NPC), priority is often given minimize dose to the critical organs at risk (OARs) to avoid potential morbid sequelae. However, in T4 NPC, dosimetric inadequacy enforced by dose constraints on OARs may significantly impact tumor control. Methods: This was a single‐institute cohort that patients diagnosed between July 2005 and December 2010 with T4 NPC treated with IMRT. All patients were re‐classification according to the 7th‐AJCC stage. Results: Overall, the average doses such as D max, D 1%, D 2% and D 1cc for various Central nervous system (CNS) OARs including brainstem, optic nerve, chiasm, temporal lobes and spinal cord were found to exceed published guidelines as RTOG0225. However, no clinical toxicities were seen during the follow‐up period except for 13% patients with temporal lobe necrosis. Conclusion: Our retrospective review showed that its feasible to maximize gross tumor volume dose coverage while exceeding most CNS OAR constraint standards, with ideal local control and no obvious increase of craniocerebral toxicity.